Algeria : 2021 Article IV Consultation-Press Release; and Staff Report; and Statement by the Executive Director for Algeria. (IMF Staff Country Reports; Country Report ;, 2021)
The concomitant Covid-19 pandemic and oil price shock in 2020 have taken a heavy toll on the Algerian economy and the population. The authorities' response helped mitigate the social and economic impact of the crisis. Nevertheless, the crisis exacerbated the Algerian economy's vulnerabilities, making even more urgent the need for a new, more inclusive and sustainable, growth model. A recovery is underway in 2021, but the outlook remains challenging. While the recent rebound in hydrocarbon prices should buoy the recovery and ease immediate financing constraints, addressing long-standing structural challenges will help to realize Algeria's vast growth potential for the benefit of its population.